Novel Experimental Method to Determine the Limit Strain by Means of Thickness Variation - Monsalve-Gonzalez, A; Saavedra-Flores, E; Iquilio-Abarzua, R; Yanez-Cart, S; Castro-Cerda, F; Guzman-Inostroza, C; Pina, J (Elsevier Ltd, 2019)
In this work an experimental method to determine the limit strain by means of digital image correlation is proposed. This method analyzes the variation of the thickness of a sheet metal through the temporal evolution of the strains, assuming incompressibility during the plastic strain process. To achieve this objective, the center and the edge of the necking area are identified with the strain history and the strain rate, respectively. The limit strain is thus determined when a non-homogeneous decrease in the thickness necking area begins, in contrast with existing methods based on performing analysis of surface strains. The proposed method is applied to determine the forming limit curve of commercial stainless steel and compared with other approaches. The results indicate that the proposed methodology is more reliable for determining the forming limit curve of the sheet, because it captures the heterogeneity of the strain distribution at the local necking site. The microstructure and the textures of the initial material are characterized via optical microscopy, x-ray diffraction and electron backscattering diffraction. The mechanical properties of the material are discussed in the light of the microstructural analysis. © 2019